The perceived value on online videogames and the construction of its consumer (Research, Society and Development, 2017)
Starting on a qualitativeapproach, we here aim at providing a study about the perception of value on the consumption of online videogames, as well as the construction of the consumer on this market.For this end,we shall make a bibliographic revision on the works of Bourdieu and McCracken, with contributions from Kotler and some punctual external observations, which shall be verified with market data study and an in-depth, non-structured interview for better understanding of the value on this kind of consumption, on its  offer as its perception by the public and as the construction of the individual that is inserted in this ambient.At the end, this publication verifies the strong social element as source of the desire on the consumption of these products and qualifies it as an essential factor for it.